The Effect of Selling Price Perception and Production Costs on the Sales Volume of Patchouli Oil at the Farmer Level in Porehu District - Nanda; Muh.Zainal; Andi Rizkiyah Hasbi (SINTA Journal (Science, Technology, and Agricultural), 2026)
This study aims to analyze the influence of farmers’ perceptions of selling prices, production costs, extension support, and information support on patchouli oil sales volume at the farmer level in Porehu District, North Kolaka Regency, Southeast Sulawesi. This study uses a quantitative approach with an associative method with 95 respondents determined through purposive sampling. Data collection used a Likert scale questionnaire and analysis was performed using multiple linear regression with SPSS. Results showed that partially, selling prices and production costs did not significantly influence patchouli oil sales volume, while extension support and information support had a positive and significant effect. Simultaneously, all variables significantly influenced sales volume (R² = 0.890).